Pengaruh Konten Pemasaran dan Kualitas Produk Terhadap Minat Beli Ulang pada Toko Aladoy di Shopee - Mohammad Wahid; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Technological progress is inevitable in life following the progress of the times and science, especially in the women's clothing sector, marketing content and product quality play an important role in attracting consumers' buying interest again. The phenomenon of increasing progress in innovation is influencing people's shopping behavior: consumers who usually shop offline are now shopping online. The Aladoy store on Shopee offers an interesting marketing content feature that the company calls live streaming as live online shopping. The aim of this research is to examine how marketing content and product quality influence consumers' willingness to repurchase. The sample selection amounted to 180 respondents using the purposive sampling method. Data was collected by distributing questionnaires. This research uses quantitative and technical data analysis methods in the form of descriptive analysis, data processing uses Partial Least Square (PLS). The results of this research show that marketing content and product quality influence the interest in repurchasing women's clothing products at the Aladoy store on Shopee.